Corruption and internal control weaknesses. Case study Romania - IONESCU, Luminiţa (Annals of Spiru Haret University. Economic Series, 2015)
Corruption represents one of the major causes of poverty all over the world and European Union is fighting against it. In the last few years, the corruption phenomenon registered a high level in some European countries and became one of the most problematic factors for doing business, due to the evolution of the perceived top five global risks: interstate conflict and regional consequences, extreme weather events, failure of national governance, state collapse or crises, high structural unemployment or underemployment (WEF-Global Risk Report 2015, p. 14). One of the modalities in combating corruption is implementing the internal control and most of the governments and organizations adopted strong control techniques. Most of the control weaknesses are related to the financial procedures and the number of controllers. Some of the controllers do not have enough financial expertise or do not understand the importance of informatics systems.